2018
DOI: 10.1002/jhet.3431
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Characterization of Quinoxaline Derivatives as a Potent Antimicrobial Agent

Abstract: A series of quinoxalinone derivatives were synthesized by the reaction of o‐phenylenediamine with oxalic acid to yield 1, 4‐dihydro quinoxaline‐2, 3‐dione (1) and then treated with thionyl chloride to yield 2, 3 dichloro quinoxaline (2). This was further reacted with hydrazine hydrate to produce 2, 3‐dihydrazinyl quinoxaline (3). This was finally reacted with substituted aromatic aldehydes to produce 2,3‐bis[2‐(sustituted benzylidine) hydrazinyl] quinoxalines (4). These quinoxalinone derivatives were character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Their extensive applications are recognized in the diverse areas of industry and pharmacology. [29][30] We then broadened our exploration, using the optimized reaction conditions for this aerobic oxygenation process. We began by investigating various substituents at the N-1 position of quinoxalin-2(1H)-ones (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Their extensive applications are recognized in the diverse areas of industry and pharmacology. [29][30] We then broadened our exploration, using the optimized reaction conditions for this aerobic oxygenation process. We began by investigating various substituents at the N-1 position of quinoxalin-2(1H)-ones (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The binding energies of all the derivatives displayed good docking scores between −8.72 and −11.29 kcal/mol. Compounds 113 a (−11.29 kcal/mol), 113 b (−11.17 kcal/mol), and 113 c (−10.85 kcal/mol) were found to represent the most promising docking score as compared with the standard DHFR inhibitor ciprofloxacin (−7.57 kcal/mol) [63] …”
Section: Pharmacological Activities Of Quinoxaline‐based Compoundsmentioning
confidence: 99%
“…Compounds 113 a (À 11.29 kcal/mol), 113 b (À 11.17 kcal/mol), and 113 c (À 10.85 kcal/mol) were found to represent the most promising docking score as compared with the standard DHFR inhibitor ciprofloxacin (À 7.57 kcal/mol). [63] El-Attar et al, reported the design, synthesis and antibacterial evaluation of some novel quinoxaline derivatives targeting dihydropteroate synthase (DHPS) (114 and 115, Figure 33). Most of the synthesized compounds demonstrated good antibacterial activities against a panel of bacterial strains.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 99%
“…Quinoxaline-2,3-diones belong to the category of many heterocycles and shown to have extensive applications in organic synthesis and material sciences. Their substantial utilization is also found in industry and pharmaceutics. Due to their salient applications, developing convenient protocols for synthesizing quinoxaline-2,3-diones has become an important research topic. Several reports are available to synthesize C-3 substituted quinoxalin-2­(1 H )-ones with diverse functionalities via direct C-3 functionalization. , The 3,4-dihydro-1,4-benzoxazin-2-one is an important heterocycle in organic synthesis and significantly used for C-3 functionalization. …”
Section: Introductionmentioning
confidence: 99%